On structural change, the social stress of a farming population, and the political economy of farm support - Oded Stark; Jan Fałkowski (University of Bonn, Center for Development Research (ZEF), 2018)
A rationale for providing support to the farm sector in the course of economic development and structural change is a growing gap between the incomes of non-agricultural workers and the incomes of farmers. Drawing on a model that enables us to analyze the level of social stress experienced by farmers as employment shifts from the farm sector to other sectors, we find that even without an increasing gap between the incomes of non-agricultural workers and the incomes of farmers, support to farmers might be needed/can be justified. This result arises because under well specified conditions, when the size of the farm population decreases, those who remain in farming experience increasing aggregate social stress. The increase is nonlinear: it is modest when the outflow from the farm sector is relatively small or when it is large, and it becomes more significant when the outflow is moderate. This finding can inform policy makers who seek to alleviate the social stress of the farming population as to the timing and intensity of that intervention.
Keywords: O13; O15; Q18; 330; Structural change; Occupational migration; Aggregate social stress; Support for farmers